Restorasi komposit kelas IV dan mahkota Richmond pasca perawatan saluran akar - I Gusti Ayu Fienna Novianthi Sidiartha; Dik Megaputri Handayani (Bali Dental Journal, 2020)
Traumatic dental injuries (TDIs) might associated with pulp injury with/without crown or root damage. In crown fracture cases, the treatment planning after injury of the permanent tooth usually determined by the vitality of the pulp and the periodontal ligament. This report is about 16-year-male patient with broken upper front teeth whom was referred to Departement of Conservative and Endodontic in Udayana Hospital. He experienced pain on those teeth and swollen gum with pus once, but they have already asymptomatic when he came to the hospital. After a comprehensive examination, the patient was treated with composite restorations on the upper left first incisor and root canal treatment on the upper right incisor along with Richmond custom dowel and Porcelain Fuse to Metal crown. A week after treatment, control of the teeth showed a good result. Traumatic dental injuries (TDIs) atau cedera traumatik dental dapat menyebabkan cedera pulpa dengan atau tanpa kerusakan mahkota atau akar. Pada kasus fraktur mahkota gigi, strategi perawatan setelah cedera pada gigi permanen ditentukan oleh vitalitas pulpa dan ligamen periodontal. Pasien laki-laki berusia 16 tahun datang ke RS UNUD dengan keluhan dua gigi depan atasnya patah. Gigi depan atas pernah sakit dan mengeluarkan nanah, namun saat ini gigi tersebut sudah tidak menimbulkan rasa sakit. Setelah dilakukan pemeriksaan komperhensif dan diagnosis, maka pasien dirawat dengan restorasi komposit kelas IV pada gigi depan kiri atas dan perawatan saluran akar pada gigi depan kanan atas disertai dengan restorasi mahkota dengan pasak Richmond. Setelah dilakukan kontrol satu minggu pasca perawatan didapatkan hasil yang baik.